2021
DOI: 10.1029/2020gb006769
|View full text |Cite
|
Sign up to set email alerts
|

Global Ocean Sediment Composition and Burial Flux in the Deep Sea

Abstract: Seafloor sediments contain information about many large-scale processes in the ocean such as surface biological productivity, particle export and degradation, hydrothermal activity, and material transport from

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 123 publications
3
45
0
1
Order By: Relevance
“… Hemispheric mercury gradients in different Pacific Ocean reservoirs. The boxplots illustrate the hemispheric gradient of ( A ) atmospheric Hg 0 model estimates (nanograms ⋅ meters −3 ) extracted at tuna sampling locations (see Materials and Methods ), ( B ) observed total Hg concentrations (picomolar) in seawater ( 12 , 34 , 38 , 53 , 54 , 56 ), ( C ) observed MeHg concentrations at peak (picomolar) in seawater ( 12 , 34 , 53 57 ), ( D ) standardized total Hg concentrations (micrograms ⋅ grams −1 , dw) in skipjack tuna (this study), and ( E ) observed total Hg concentrations (nanograms ⋅ grams −1 , dw) in marine sediments ( 2 , 73 78 ). ** indicates significant differences between the northern and southern hemispheres (Kruskal–Wallis test; P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“… Hemispheric mercury gradients in different Pacific Ocean reservoirs. The boxplots illustrate the hemispheric gradient of ( A ) atmospheric Hg 0 model estimates (nanograms ⋅ meters −3 ) extracted at tuna sampling locations (see Materials and Methods ), ( B ) observed total Hg concentrations (picomolar) in seawater ( 12 , 34 , 38 , 53 , 54 , 56 ), ( C ) observed MeHg concentrations at peak (picomolar) in seawater ( 12 , 34 , 53 57 ), ( D ) standardized total Hg concentrations (micrograms ⋅ grams −1 , dw) in skipjack tuna (this study), and ( E ) observed total Hg concentrations (nanograms ⋅ grams −1 , dw) in marine sediments ( 2 , 73 78 ). ** indicates significant differences between the northern and southern hemispheres (Kruskal–Wallis test; P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Using a compilation of Th-normalized mass AR (Hayes et al, 2020(Hayes et al, , 2021, a minimum estimate of the global marine Ba output flux in >1,000 m water depth, via the burial of pBa xs , is ∼19 ± 10 Gmol year −1 . The inventory of dBa in the ocean is ∼150 Tmol.…”
Section: Marine Barium Cyclementioning
confidence: 99%
“…This dissolution not only includes the 11-21 Gt/a of the riverine solid sediment flux (adding 3.8 Gt/a of Si; Viers et al, 2009) but also the 0.6-2.4 Gt/a of the rock coast input solid sediment flux (results from this work, upscaled at the global scale, see Supplementary Material). Since Si is a limiting element in much of the ocean, a larger Si flux would rapidly be assimilated by the local biology (Fripiat et al, 2011), accelerating its uptake from ocean water and sedimentation (0.15 Gt/a or 5.3 Tmol/a; Hayes et al, 2021). In the case of the Fe cycle, the mass budget imbalance is not as clear, but increasing the rock coast sediment flux by a factor 3 to 12 would make it a major Fe source (extrapolating from Raiswell et al, 2006, 12-30% of the Fe reaching the continental shelf would come from coastal erosion).…”
Section: Discussionmentioning
confidence: 99%